Peningkatan Pengetahuan Tentang Gizi Seimbang pada Siswa siswi di SMPN 1 Peringgarata Lombok Tengah - Ardian, Junendri; Jauhari, M. Thonthowi; Rahmiati, Baiq Fitria; Naktiani, Wayan Canny; Solehah, Novia Zuriatun (Insan Kreasi Media, 2023)
Adolescents are prone to nutritional problems, specific malnutrition problems such as anemia and overweight can also be experienced by adolescents. Nutritional problems in adolescents can occur due to bad eating patterns, this stems from a lack of knowledge about balanced nutrition among adolescents. The implementation of this community service was carried out with a pretest and posttest design regarding balanced nutritional knowledge of students, in addition to that, nutritional status assessments and nutritional consultations were also carried out for students as targets. To measure the success of the activity, the service team held a quiz pre- and post-test by answering questions, after which a nutrition consultation was carried out. From the pre-test results it was found that students' knowledge about hypertension in adolescents was still very low, while the post-test results showed an increase in students' knowledge about balanced nutrition. This community service shows that knowledge about balanced nutrition in adolescents can be increased through education about the importance of adolescents knowing the intake of good nutrition according to their needs and age.